Anatomical changes of Akar Putra chicken digestive system after partial ablation of uropygial gland - Jawad, Hasan S. A.; Idris, Lokman Hakim; Abu Bakar @ Zakaria, Md Zuki; Kasim, Azhar (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The current study proposes anatomical changes in the digestive system of 120 Akar Putra chicken after surgical removing of an uropygial gland. The experiment comprised five treatments (24 chicken/ treatment), with 3 replicates for each (8 chicken/ replicate). Experimental treatments consist of a control treatment T1; partial ablation of the uropygial gland were applied on T2, T3, T4 and T5 treatments at 3, 4, 5 and 6 weeks of age respectively. The results presents that males of partial uropygialectomy (PU) treatments had (P<0.01) longer esophagus 9.9-16.2%, proventriculus 11.1- 34.4%, gizzard 26.7-220%, pancreas 0-20.4%, jejunum 4.9-26.1 and colon 18.1-60.6 than their control group counterparts. Furthermore, females of PU treatments had (P<0.01) longer esophagus 6.8-22.3%, pancreas 8.3-33.3% and cecum 13-26% compared with females in control. In contrast, total GIT weight were 21.2 to 78.8% heavier (P < 0.01) in males of PU treatments, mainly in the esophagus, duodenum, pancreas, jejunum, ilium and cecum. No significant impact (P>0.05) between treatments was recorded in the total females GIT weight; however, females of PU treatments had 5.9-41.2% heavier ilium (P<0.01) and 11.1-77.8% heavier cecum (P<0.01). Total GIT density, did not show significant different (P>0.05) between treatments in females. Nevertheless, it was highly different (P<0.01) for males of PU treatments, mainly in esophagus (P<0.05), gizzard (P<0.05), pancreas (P<0.01) and cecum (P<0.05). This new characterization of treatments shows that divergent selection based on modified the morphology of most GIT parts, suggesting greater activity of this compartment in PU treatments' bird than control bird.